HIV Infected T Cells Can Proliferate in vivo Without Inducing Expression of the Integrated Provirus - Musick, Andrew; Spindler, Jonathan; Boritz, Eli; Pérez, Liliana; Crespo-Vélez, Daniel; Patro, Sean C.; Sobolewski, Michele D.; Bale, Michael J.; Reid, Carolyn; Keele, Brandon F.; Capoferri, Adam; Shao, Wei; et al. (Frontiers in Microbiology, 2019)
Background: HIV-1 proviruses can persist during ART in clonally-expanded populations of CD4+ T cells. To date, few examples of an expanded clones containing replication-competent proviruses exist, although it is suspected to be common. One such clone, denoted AMBI-1 (1), was also a source of persistent viremia on ART, begging the question of how the AMBI-1 clone can survive despite infection with a replication-competent, actively-expressing provirus. We hypothesized that only a small fraction of cells within the AMBI-1 clone are activated to produce virus particles during cell division while the majority remain latent despite division, ensuring their survival. To address this question, we determined the fraction of HIV-1 proviruses within the AMBI-1 clone that expresses unspliced cell-associated RNA during ART and compared this fraction to 33 other infected T cell clones within the same individual. Results: In total, 34 different clones carrying either intact or defective proviruses in “Patient 1” from Maldarelli, et al. (1) were assessed. We found that 2.3% of cells within the AMBI-1 clone contained unspliced HIV-1 RNA. Highest levels of HIV-1 RNA were found in the effector memory T cell subset. The fraction of cells within clones that contained HIV-1 RNA was not different in clones with intact (median 2.3%) vs. defective (median 3.5%) proviruses (p=0.2). However, higher fractions and levels of RNA were found in cells with proviruses containing multiple drug resistance mutations, including those contributing to rebound viremia. Conclusions: These findings show that the vast majority of HIV-1 proviruses within expanded T cell clones, including intact proviruses, may be transcriptionally silent at any given time, implying that infected T cells may be able to be activated to proliferate without inducing the expression of the integrated provirus or, alternatelively, may be able to proliferate without cellular activation. The results of this study suggest that the long, presumed correlation between the level of cellular and proviral activation may not be accurate and, therefore, requires further investigation.